Desenvolvimento de método para determinação multielementar em chocolate artesanal por ICP OES e ICP-MS utilizando a extração assistida por ultrassom para o preparo da amostra - Santana, Giovanna Fonseca Rosa (2023)
This research aims to establish a sample preparation method via ultrasound-assisted extraction to determine As, Ca, Cd, Fe, K, Mg, Mn, Na, P, Pb and Zn in artisanal chocolates with different cocoa contents (46%, 65%, 70% and 85%). To develop the preparation method, the reagents HNO3, HCl and CH2O2 were used in a simplexcentroid Mixture Planning, originating seven extractor solutions assuming the volume of acids as variables, totaling four different plans, one for each acid content. cocoa. The concentration of the extracting solutions, mass of the samples and ultrasound conditions were fixed, assuming a concentration of 2 mol.L-1 , approximately 200 mg of sample and an ultrasound bath at 50 ± 5°C for 10 minutes, respectively. The samples were verified using Optical Emission Spectrometry with Inductively Coupled Plasma (Ca, Fe, K, Mg, Mn, Na, P and Zn) and Mass Spectrometry with Inductively Coupled Plasma (As, Cd and Pb) and, at from the data obtained, the mathematical model calculated, and the contour graph plotted. The data was also subjected to Principal Component Analysis (PCA). The results obtained in the multivariate analyzes indicate better efficiency for extracting the elements in 200 mg of samples when using a solution of 10.0 mL of HNO3 2.0 mol.L-1 , with an ultrasonic bath of approximately 50°C for 10 minutes, followed by centrifugation at 3800 rpm also for 10 minutes. The method was evaluated against its figures of merit, including linearity, limit of detection and quantification, precision and accuracy. The results demonstrate that the method has adequate sensitivity, with low detection and quantification limits, in addition to presenting satisfactory precision in determining the elements analyzed. When investigating the accuracy of the method, the results obtained from the analysis of the certified reference material Baking Chocolate SRM 2384 were analyzed. An agreement was found between the certified values and the values obtained for Ca, Fe, Mn, P and Zn, and an excellent recovery for all analytes when compared to validated methods. The proposed method was used to analyze 39 samples of artisanal chocolate of different levels and manufacturers. The results were subjected to a PCA, in which it was found that chocolates with cocoa levels below 60% and which contained milk in their composition had high concentrations of Ca and Na, while samples with levels above 60% and without milk demonstrated higher concentrations of K and P. Among the samples evaluated, PCA was also applied to 17 samples from two different producers to evaluate the influence of cocoa content and the region of chocolate production. The results demonstrate a possible influence of the location of the planting cocoa in the presence of micronutrients and their concentrations in the product. Furthermore, 8 samples containing Pb were identified, 4 of which exceeded the maximum limit established by resolution nº 42 of August 2013 (0.40mg.kg-1 ). Based on the results obtained throughout the study, it is concluded that the method developed is efficient for the analysis of artisanal chocolates, and can be applied to samples with different cocoa contents, without resulting in significant loss of data.